Tumor cell cholesterol depletion and V-ATPase inhibition as an inhibitory mechanism to prevent cell migration and invasiveness in melanoma - Costa, Gildeíde Aparecida; de Souza, Sávio Bastos; da Silva Teixeira, Layz Ribeiro; Okorokov, Lev A.; Arnholdt, Andrea Cristina Vetö; Okorokova-Façanha, Anna L.; Façanha, Arnoldo Rocha (Biochimica et biophysica acta, 2018)
V-ATPase interactions with cholesterol enriched membrane microdomains have been related to metastasis in a variety of cancers, but the underlying mechanism remains at its beginnings. It has recently been reported that the inhibition of this H+ pump affects cholesterol mobilization to the plasma membrane. Inhibition of melanoma cell migration and invasiveness was assessed by wound healing and Transwell assays in murine cell lines (B16F10 and Melan-A). V-ATPase activity was measured in vitro by ATP hydrolysis and H+ transport in membrane vesicles, and intact cell H+ fluxes were measured by using a non-invasive Scanning Ion-selective Electrode Technique (SIET). Cholesterol depletion by 5mM MβCD was found to be inhibitory to the hydrolytic and H+ pumping activities of the V-ATPase of melanoma cell lines, as well as to the migration and invasiveness capacities of these cells. Nearly the same effects were obtained using concanamycin A, a specific inhibitor of V-ATPase, which also promoted a decrease of the H+ efflux in live cells at the same extent of MβCD. We found that cholesterol depletion significantly affects the V-ATPase activity and the initial metastatic processes following a profile similar to those observed in the presence of the V-ATPase specific inhibitor, concanamycin. The results shed new light on the functional role of the interactions between V-ATPases and cholesterol-enriched microdomains of cell membranes that contribute with malignant phenotypes in melanoma. •V-type H+-ATPase activity is dependent on cholesterol membrane microdomains•Cholesterol depletion inhibits H+ efflux in live tumor cells•This disrupts extracellular and cytoplasmic pH signatures required for tumor cell migration and invasion